Sepaksila Skills of Tombonan Sepak Takraw Players : The Role of Physical Conditions (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2023)
The purpose of the study was to determine the relationship between physical condition and soccer skills. This study used quantitative methods with correlational descriptive research. The population in this study is players of Tombonan sepak takraw club. The sampling technique used is porpusive sampling, which is a certain consideration by the researcher. Since there are 15 Tombonan sepak takraw club players, all were sampled in the study.The test instruments used in this study were physical condition tests (eye-foot coordination and balance), soccer skills tests. The result of the study was that the role of physical condition had a significant relationship with the sepaksila skills of Sepak Takraw Tomonan players with a significant value of 0.000>0.05. The conclusion is that the variable physical condition greatly determines the success of a sepak takraw player in performing the soccer technique.